2017
DOI: 10.14309/crj.2017.68
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse Large B-Cell Lymphoma with Secondary Hemophagocytic Lymphohistiocytosis Presenting as Acute Liver Failure

Abstract: Hemophagocytic lymphohistiocytosis (HLH) and newly diagnosed malignant infiltration of liver are rare presentations of acute liver failure associated with poor prognosis. We report a case of a patient with acute liver failure caused by malignant infiltration by diffuse large B-cell lymphoma and secondary HLH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 18 publications
(15 reference statements)
0
10
0
1
Order By: Relevance
“…Of note, ALF due to diffuse large B-cell lymphoma is reported to account for only 0.26% (5/1910) [1]; to date, only ten cases of ALF due to diffuse large B-cell lymphoma have been reported (Table 1) [6][7][8][9][10][11][12][13][14][15], with the time to death following admission in six reported cases being 5 days [12,13], 8 days [7,9], 14 days [14], and 19 days [6], in contrast to only 3 days in the present case. It has been reported that the deaths were caused by multi-organ failure involving cardiovascular collapse, acute lung injury, and renal failure, in addition to hepatic failure [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, ALF due to diffuse large B-cell lymphoma is reported to account for only 0.26% (5/1910) [1]; to date, only ten cases of ALF due to diffuse large B-cell lymphoma have been reported (Table 1) [6][7][8][9][10][11][12][13][14][15], with the time to death following admission in six reported cases being 5 days [12,13], 8 days [7,9], 14 days [14], and 19 days [6], in contrast to only 3 days in the present case. It has been reported that the deaths were caused by multi-organ failure involving cardiovascular collapse, acute lung injury, and renal failure, in addition to hepatic failure [5].…”
Section: Discussionmentioning
confidence: 99%
“…8 [13] 2017 57 M CT: hepatic steatosis, splenomegaly with multiple splenic infarcts, and lymphadenopathy…”
Section: Discussionmentioning
confidence: 99%
“…HLH occurs in about 1% of hematologic malignancies[ 12 , 13 ]; sometimes from chemotherapy for these malignancies[ 14 ]. Patients with malignancy have extremely high mortality, partly due to delayed diagnosis of HLH[ 15 , 16 ]. Suggested mechanisms of HLH associated with malignancy include: profound inflammation from immune activation, persistent antigen stimulation by cancer cells, and deranged immune response secondary to chemotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…The primary form, usually seen in infants and children, results from genetic missense mutations in the perforin genes, responsible for NK cell and cytotoxic T lymphocyte function. 8,9 Secondary haemophagocytic lymphohistiocytosis, seen in adults, is caused by infections, malignancy, rheumatological and metabolic diseases. Epstein-Barr virus is the most consistent, in up to a third of secondary haemophagocytic lymphohistiocytosis.…”
Section: Discussionmentioning
confidence: 99%